Forefront of Na+/Ca2+ Exchanger Studies: Molecular Pharmacology of Na+/Ca2+ Exchange Inhibitors - Takahiro Iwamoto (Elsevier, 2004)
The Na+/Ca2+ exchanger (NCX) is an ion transporter that exchanges Na+ and Ca2+ in either Ca2+ efflux or Ca2+ influx mode, depending on membrane potential and transmembrane ion gradients. In myocytes, neurons, and nephron cells, NCX is thought to play an important role in the regulation of intracellular Ca2+ concentration. Recently, the benzyloxyphenyl derivatives KB-R7943, SEA0400, and SN-6 have been developed as selective NCX inhibitors. Currently, SEA0400 is the most potent and selective inhibitor. These inhibitors possess different isoform-selectivities, although they have similar properties, such as Ca2+ influx mode-selectivity and I1 inactivation-dependence. Recent site-directed mutagenesis has revealed that these inhibitors possess some molecular determinants (Phe-213, Val-227, Tyr-228, Gly-833, and Asn-839) for interaction with NCX1. These benzyloxyphenyl derivatives are expected to be useful tools to study the physiological roles of NCX. Moreover, such inhibitors may have therapeutic potential as a new remedy for ischemic disease, arrhythmias, heart failure, and hypertension. Keywords:: Na+/Ca2+ exchanger (NCX), NCX inhibitor, inhibitory mechanism, ischemia/reperfusion injury